Pengaruh Intellectual Capital dan Enterprise Risk Management Terhadap Nilai Perusahaan dengan Kinerja Keuangan sebagai Variabel Intervening (pada Perusahaan Farmasi yang Terdaftar di Bursa Efek Indonesia Periode 2018-2021) - lestari, Cipta Visi; Wediawati, Besse; Setiawati, Rike (Universitas Batanghari Jambi, 2024)
Price book value is an indicator of company value that is usually used as an assessment by investors when investing. This research aims to obtain the results of a study of the influence of intellectual capital with the value added intellectual capital (VAIC) indicator and enterprise risk management with the indicator (COSO ERM) on company value and financial performance as intervening variables in pharmaceutical sector companies listed on the Indonesia Stock Exchange for the 2018 period. -2021. The method used was purposive sampling so that a sample of 9 companies was obtained. Data analysis uses partial least squares (PLS). The research results show that intellectual capital, enterprise risk management and financial performance directly have a positive and significant effect on company value. The research results also state that intellectual capital and enterprise risk management which are mediated by financial performance variables have a positive influence on company value.